Prevention of COVID-19 in the 2020-2021 biennium: recommendations on hygiene habits established by the Ministry of Health (Research, Society and Development, 2022)
The study aimed to discuss the hygiene habits recommended by the Ministry of Health after the COVID-19 pandemic that are considered important by the population. The methodology is a narrative review, with a descriptive qualitative approach, with the research question: what are the hygiene habits after the COVID-19 pandemic recommended by the Ministry of Health, which are considered important by the population, especially in respiratory disease? Articles were sought, using the following inclusion criteria: articles in Portuguese, in the time frame from 2017 to 2022, with reference to the Brazilian territory, that portrayed hygiene habits in the face of COVID-19, whose result showed 18 articles and 09 documents from the Ministry of Health, in which the thematic unit emerged: hygiene habits after the COVID-19 pandemic recommended by the Ministry of Health, especially in respiratory disease and the categories: 1: hygiene habits recommended by the Ministry of Health during the COVID-19 pandemic; 2: the context of hygiene habits used by the population during the COVID-19 pandemic, which allowed for a robust and consistent discussion. It was concluded that hygiene habits after the COVID-19 pandemic, recommended by the Ministry of Health, are considered important, but government support is needed so that the entire population has access to drinking water, considering the need for more political initiatives, government agencies, allied to the support of civil society.